High-toughness jet mortar as well as preparation method and application thereof
By adding inorganic nanomaterials and polymers to the spray mortar, the problem of reduced compressive strength after polymer incorporation is solved, the compressive and flexural strength of fiber cement mortar is improved, and the safety of tunnel and slope structures is enhanced .
Patent Information
- Application Number
- CN202411378091.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, the problem of the reduction of compressive strength after polymers are incorporated into fiber cement mortar has affected the safety of tunnel and slope structures.
By adding inorganic nanomaterials to the spray mortar, the pores inside the mortar are optimized by using their nucleation and filling effects, combining the bridging of polymer film and fibers, the compressive strength and toughness of the mortar are improved.
The polymer incorporation does not affect the compressive strength of the fiber cement mortar, and at the same time improves the mechanical properties of the mortar. The flexural strength can be controlled at 13-15 MPa in 28 days, and the compressive strength can be controlled at 45-60 MPa. Significantly improves the durability and toughness of the mortar.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a high-toughness spray mortar and a preparation method and application thereof. Background Art
[0002] With the continuous improvement of urbanization, tunnel structures have been widely used in urban construction, transportation, energy, national defense engineering and other aspects. At the same time, the safety of tunnel structures under seismic loads has also attracted more and more attention and attention from scholars. Tunnel structures are usually considered to be low-toughness structures. Once an accident occurs, there is a high risk of large-scale damage or even continuous collapse due to local damage. Sprayed mortar + steel mesh support is often used in tunnel and slope support. The mechanical properties of sprayed mortar are related to the safety of tunnel and slope structures. Although the steel mesh can make up for the defects of low tensile strength and high brittleness of sprayed mortar. However, cracks will still appear when the mortar encounters dynamic loads such as earthquakes, and the expansion of cracks will accelerate structural damage.
[0003] Traditional sprayed mortar mostly uses fiber cement mortar, and the types of fibers include steel fibers, polymer fibers or plant fibers. The presence of fibers will block the expansion of cracks, thereby delaying the destruction of the structure. In order to further improve the toughness of fiber cement mortar and the adhesion between it and the steel bars or substrate, a certain amount of polymer can be added to the fiber cement mortar to prepare polymer-fiber cement mortar. However, although the addition of polymer increases the toughness of the mortar, it significantly reduces the compressive strength of the mortar. This is mainly because the addition of polymer plays an air entraining role and increases the internal porosity of the mortar. In addition, polymers are elastic materials that will also reduce the compressive strength. After the polymer is added, it will affect the hydration reaction of cement.
[0004] Patent CN109694231A discloses a magnesium-phosphate-based cement spraying material, a preparation method and application thereof, patent CN104556883A discloses an anti-skid cement mortar and a preparation method thereof, patent CN101538136A discloses a premixed mortar with high water retention and a production method thereof, and patent CN112794686A discloses a waterproof dry-mixed mortar and a production process thereof. However, the current prior art still has the problem of reduced compressive strength of fiber cement mortar after polymer incorporation. Summary of the invention
[0005] The purpose of the present invention is to provide a high-toughness sprayed mortar and its preparation method and application in order to solve at least one of the above-mentioned problems, so as to solve the problem of decreased compressive strength caused by the addition of polymer to fiber cement mortar in the prior art, and to achieve that the addition of polymer does not affect the compressive strength of the fiber cement mortar, while further improving the mechanical properties of the fiber cement mortar.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a high-toughness sprayed mortar, which includes, by weight, 30-50 parts of cement, 90-150 parts of fine aggregate, 1-2 parts of fiber, 3-10 parts of polymer, 0.015-0.75 parts of inorganic nanomaterials, 0.3-1.5 parts of water reducer and 10-30 parts of water.
[0008] Furthermore, in parts by weight, the mortar includes 50 parts of cement, 150 parts of fine aggregate, 1.44 parts of fiber, 5 parts of polymer, 0.75 parts of inorganic nanomaterial, 1 part of water reducing agent and 22.5 parts of water.
[0009] Furthermore, in parts by weight, the mortar includes 50 parts of cement, 150 parts of fine aggregate, 1.44 parts of fiber, 5 parts of polymer, 0.075 parts of inorganic nanomaterial, 1 part of water reducing agent and 22.5 parts of water.
[0010] Furthermore, the inorganic nanomaterial includes any one of nano-silicon dioxide and carbon nanotubes.
[0011] Furthermore, the inorganic nanomaterial is inorganic nanoparticles.
[0012] Furthermore, the polymer includes any one of ethylene-vinyl acetate copolymer, styrene-acrylate copolymer and butadiene-styrene copolymer.
[0013] Furthermore, the polymer exists in the form of rubber powder.
[0014] Furthermore, the fiber includes any one of polypropylene fiber and polyvinyl alcohol fiber.
[0015] Furthermore, the cement is early strength silicate cement.
[0016] Furthermore, the early strength silicate cement includes any one of P·I 42.5R silicate cement, P·I 52.5R silicate cement, P·II 42.5R silicate cement and P·II 52.5R silicate cement.
[0017] Furthermore, the fine aggregate includes one or both of river sand and machine-made sand.
[0018] Furthermore, the water reducer is a polycarboxylate water reducer.
[0019] The nucleation effect of inorganic nanomaterials can promote the hydration reaction of cement, and the filling effect of inorganic nanomaterials is beneficial to optimize the internal pores of mortar, improve the mechanical properties of mortar and enhance the durability of mortar. The present invention mainly utilizes the filling and nucleation effects of inorganic nanomaterials to improve the compressive strength of polymer-fiber cement mortar; the film formed by the polymer can be adsorbed on the fiber surface to promote the bonding between the fiber and the mortar, which is beneficial to further improve the toughness of the fiber cement mortar, and utilizes the bridging crack effect of polymer film, nanoparticles and fibers at different scales to improve the toughness of the mortar.
[0020] The second technical solution of the present invention is to provide a method for preparing the high-toughness sprayed mortar as described above, the preparation method comprising: mixing cement, fine aggregate and polymer into a dry mix, adding fiber and mixing evenly to obtain a fiber dry mix, mixing a water reducer and water into a mixed liquid, adding the dry mix thereto, adding the inorganic nanomaterial to the dry mix or the mixed liquid, mixing, and stirring to obtain the high-toughness sprayed mortar.
[0021] Furthermore, the inorganic nanomaterial is mixed with cement, fine aggregate and polymer as a dry mix to obtain the sprayed mortar; or the inorganic nanomaterial is mixed with a water reducing agent and water as a mixed liquid, and the sprayed mortar is obtained after dispersion.
[0022] Furthermore, the preparation method includes: mixing cement, fine aggregate, nano-silicon dioxide and polymer powder to prepare a dry mix, then slowly adding fibers to the dry mix in batches, continuously stirring the dry mix during the adding process so that the fibers can be fully dispersed in the dry mix, mixing to obtain a fiber dry mix, mixing a water reducer and water into a mixed liquid, adding the mixed liquid to a wet mixing pot, and then adding the fiber dry mix to mix, thereby obtaining the high-toughness spray mortar.
[0023] Furthermore, the preparation method includes: mixing cement, fine aggregate and polymer powder to prepare a dry mix, then slowly adding fibers to the dry mix in batches, constantly stirring the dry mix during the adding process so that the fibers can be fully dispersed in the dry mix, mixing to obtain a fiber dry mix, mixing a water reducer, carbon nanotubes and water to form a mixed liquid, adding the mixed liquid into a wet stirring pot after dispersion, and then adding the fiber dry mix to mix, so as to obtain the high-toughness spray mortar.
[0024] Furthermore, the dispersion includes any one of ultrasonic dispersion and high-speed shear dispersion.
[0025] Furthermore, the dispersion is ultrasonic dispersion for 10-20 minutes, preferably 15 minutes.
[0026] The third technical solution of the present invention is to provide an application of the high-toughness sprayed mortar as described above in tunnel or slope support.
[0027] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0028] Compared with the prior art, the present invention has the following advantages:
[0029] 1. The present invention adds inorganic nanomaterials during the preparation of the sprayed mortar. The nucleation effect of the inorganic nanomaterials can promote the hydration reaction of cement. The filling effect of the inorganic nanomaterials is beneficial to optimizing the internal pores of the mortar, improving the mechanical properties of the mortar and enhancing the durability of the mortar. The present invention utilizes the filling and nucleation effects of inorganic nanoparticles to improve the compressive strength of the polymer-fiber cement mortar, thereby solving the defect that the addition of polymers will reduce the compressive strength of the fiber cement mortar.
[0030] 2. The present invention utilizes the filling and nucleation effects of inorganic nanoparticles to improve the compressive strength of polymer-fiber cement mortar, and utilizes the bridging crack effects of polymer films, nanoparticles and fibers at different scales to improve the toughness of the mortar, thereby preparing a sprayed mortar with stronger mechanical properties. Compared with traditional sprayed mortar (fiber cement mortar or polymer-fiber cement mortar), the sprayed mortar of the present invention has higher flexural strength and compressive strength. Experiments show that the 28-day flexural strength of the mortar can be controlled between 13-15 MPa, and the compressive strength can be controlled between 45-60 MPa.
[0031] 3. The sprayed mortar of the present invention utilizes water reducing agent and polymer to improve the working performance of fiber cement mortar and promote the dispersion of fibers in the mortar, and utilizes water reducing agent to promote the dispersion of nanoparticles such as carbon nanotubes in the mortar.
[0032] 4. The preparation process of the sprayed mortar described in the present invention is simple, and the required material types are few, easy to obtain, and easy to implement. The prepared sprayed mortar has low cost and excellent mechanical properties, which is conducive to expanding production. DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0034] Unless otherwise specified, the experimental reagents and raw materials used in the present invention are commercially available.
[0035] The experimental methods without specific conditions in the following implementations are all selected according to conventional methods and conditions, or according to the product instructions. Unless otherwise specified, the experimental instruments used in the present invention are all conventional experimental instruments in the laboratory.
[0036] Example 1
[0037] The present embodiment provides a high-toughness sprayed mortar and a preparation method thereof. In parts by weight, the mortar includes 50 parts of cement, 150 parts of fine aggregate, 1.44 parts of fiber, 5 parts of polymer, 0.75 parts of inorganic nanomaterials, 1 part of water reducer and 22.5 parts of water.
[0038] The preparation method of the high-toughness sprayed mortar in the above-mentioned embodiment 1 is as follows:
[0039] P·II 52.5R silicate cement, river sand, nano silicon dioxide and ethylene-vinyl acetate copolymer rubber powder are mixed to prepare a dry mix, and then polyvinyl alcohol fiber is added to the dry mix slowly in batches, and the dry mix is continuously stirred during the adding process so that the fiber can be fully dispersed in the dry mix, and the fiber dry mix is mixed to obtain a fiber dry mix, and a polycarboxylate water reducer is mixed with water to obtain a mixed liquid, and the mixed liquid is added to a wet stirring pot, and then the fiber dry mix is added and stirred to obtain the high-toughness spray mortar.
[0040] Example 2
[0041] The present embodiment provides a high-toughness sprayed mortar and a preparation method thereof. In parts by weight, the mortar includes 50 parts of cement, 150 parts of fine aggregate, 1.44 parts of fiber, 5 parts of polymer, 0.075 parts of inorganic nanomaterials, 1 part of water reducer and 22.5 parts of water.
[0042] The preparation method of the high-toughness sprayed mortar in the above-mentioned Example 2 is as follows:
[0043] P·II 52.5R silicate cement, river sand and ethylene-vinyl acetate copolymer rubber powder are mixed to prepare a dry mix, and then polyvinyl alcohol fiber is added to the dry mix slowly in batches, and the dry mix is continuously stirred during the adding process so that the fiber can be fully dispersed in the dry mix, and the fiber dry mix is mixed to obtain a fiber dry mix, and a polycarboxylate water reducer, carbon nanotubes and water are mixed to obtain a mixed liquid, and after ultrasonic dispersion for 15 minutes, the mixed liquid is added to a wet stirring pot, and then the fiber dry mix is added and stirred to obtain the high-toughness spray mortar.
[0044] In this embodiment, except that the inorganic nanomaterial is selected as carbon nanotubes, the rest is the same as that of the embodiment 1.
[0045] Example 3
[0046] The present embodiment provides a high-toughness sprayed mortar and a preparation method thereof. In parts by weight, the mortar includes 50 parts of cement, 150 parts of fine aggregate, 1.44 parts of fiber, 5 parts of polymer, 0.75 parts of inorganic nanomaterials, 1 part of water reducer and 22.5 parts of water.
[0047] In this embodiment, except that the polymer is selected as styrene-acrylate copolymer, the rest is the same as that of embodiment 1.
[0048] Example 4
[0049] The present embodiment provides a high-toughness sprayed mortar and a preparation method thereof. In parts by weight, the mortar includes 50 parts of cement, 150 parts of fine aggregate, 1.44 parts of fiber, 5 parts of polymer, 0.75 parts of inorganic nanomaterials, 1 part of water reducer and 22.5 parts of water.
[0050] In this embodiment, except that the fiber is selected as polypropylene fiber, the rest is the same as that of embodiment 1.
[0051] Example 5
[0052] The present embodiment provides a high-toughness sprayed mortar and a preparation method thereof. In parts by weight, the mortar includes 50 parts of cement, 150 parts of fine aggregate, 1.44 parts of fiber, 5 parts of polymer, 0.75 parts of inorganic nanomaterials, 1 part of water reducer and 22.5 parts of water.
[0053] In this embodiment, except that the cement is selected as P·I 52.5R Portland cement, the rest is the same as that of Embodiment 1.
[0054] Example 6
[0055] The present embodiment provides a high-toughness sprayed mortar and a preparation method thereof. In parts by weight, the mortar includes 50 parts of cement, 150 parts of fine aggregate, 1.44 parts of fiber, 5 parts of polymer, 0.75 parts of inorganic nanomaterials, 1 part of water reducer and 22.5 parts of water.
[0056] In this embodiment, except that the fine aggregate is selected as machine-made sand, the rest is the same as that of Embodiment 1.
[0057] Comparative Example 1-2:
[0058] In order to verify the effect of the present invention, comparative examples 1-2 are set, and the raw material group distribution ratio comparison between embodiment 1-2 and comparative example 1-2 is shown in Table 1:
[0059] In the table, Example 1 is nano-silicon dioxide-polymer-fiber sprayed cement mortar, Example 2 is carbon nanotube-polymer-fiber sprayed cement mortar, Comparative Example 1 is fiber cement mortar, and Comparative Example 2 is polymer-fiber cement mortar.
[0060] Table 1 Raw material composition ratio of Example 1-2 and Comparative Example 1-2
[0061] raw material model Example 1 Example 2 Comparative Example 1 Comparative Example 2 cement P·II 52.5R Portland cement 50 50 50 50 fine aggregate river sand 150 150 150 150 fiber Polyvinyl alcohol fiber 1.44 1.44 1.44 1.44 polymer Ethylene-vinyl acetate copolymer 5 5 - 5 Inorganic Nanomaterials1 Nano Silica 0.75 - - - Inorganic Nanomaterials 2 Carbon Nanotubes - 0.075 - - Water reducing agent Polycarboxylate water reducer 1 1 1 1 water - 22.5 22.5 22.5 22.5
[0062] Then, Examples 1-6 and Comparative Examples 1-2 were tested as follows:
[0063] The mechanical properties of cement mortar were evaluated for Examples 1-6 and Comparative Examples 1-2: the flexural and compressive strengths were determined with reference to GB / T17671-2021 (ISO679:2009) "Test method for strength of cement mortar (ISO method)".
[0064] The mechanical properties of Examples 1-2 and Comparative Examples 1-2 are shown in Table 2 below, and the mechanical properties of Examples 4-6 are close to those of Example 1. As can be seen from Table 2, the compressive strength, flexural strength and fold-to-compression ratio of the sprayed mortar (Examples 1 and 2) prepared in this example are significantly improved compared to the fiber cement mortar in Comparative Example 1; compared to the improved polymer-fiber cement mortar in Comparative Example 2, its compressive strength and flexural strength are also significantly improved. The 28-day flexural strength of the sprayed mortar prepared in this example can be controlled between 13-15 MPa, the compressive strength can be controlled between 45-60 MPa, and the fold-to-compression ratio is increased by up to 26.8%.
[0065] Table 2 Mechanical properties of sprayed mortar of Example 1-2 and Comparative Example 1-2
[0066] Test items Example 1 Example 2 Comparative Example 1 Comparative Example 2 28-day compressive strength (MPa) 49.76 46.39 42.83 42.12 28-day flexural strength (MPa) 13.10 13.83 9.94 12.14 28-day fold-to-pressure ratio 0.263 0.298 0.235 0.288
[0067] In summary, compared with the prior art, the high-toughness sprayed mortar of the present invention has stronger flexural strength and compressive strength, and can be used for tunnel or slope support.
[0068] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A high-toughness spray mortar, characterized in that: In parts by weight, the mortar comprises 30-50 parts of cement, 90-150 parts of fine aggregate, 1-2 parts of fiber, 3-10 parts of polymer, 0.015-0.75 parts of inorganic nanomaterial, 0.3-1.5 parts of water reducer and 10-30 parts of water.
2. A high-toughness spray mortar according to claim 1, characterized in that: The inorganic nanomaterial includes any one of nano silicon dioxide and carbon nanotube.
3. The high-toughness spray mortar according to claim 1, characterized in that: The polymer includes any one of ethylene-vinyl acetate copolymer, styrene-acrylate copolymer and butadiene-styrene copolymer.
4. The high-toughness spray mortar according to claim 1, characterized in that: The fiber includes any one of polypropylene fiber and polyvinyl alcohol fiber.
5. The high-toughness sprayed mortar according to claim 1, characterized in that: The cement is early strength type silicate cement.
6. The high-toughness sprayed mortar according to claim 1, characterized in that: The fine aggregate includes one or both of river sand and machine-made sand.
7. The high-toughness sprayed mortar according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.
8. A method for preparing the high-toughness sprayed mortar according to claim 1, characterized in that: The preparation method comprises: mixing cement, fine aggregate and polymer into a dry mix, adding fiber and mixing evenly to obtain a fiber dry mix, mixing a water reducer and water into a mixed liquid, adding the dry mix thereto, adding the inorganic nanomaterial into the dry mix or the mixed liquid, mixing, and stirring to obtain the high-toughness sprayed mortar.
9. The method for preparing high-toughness sprayed mortar according to claim 8, characterized in that: The inorganic nano material is mixed with cement, fine aggregate and polymer as a dry mixture to obtain the sprayed mortar; or the inorganic nano material is mixed with a water reducing agent and water as a mixed liquid, and the sprayed mortar is obtained after dispersion.
10. Use of the high-toughness sprayed mortar as claimed in claim 1 in tunnel or slope support.
Citation Information
Patent Citations
Premixing mortar with high moisture retention and production method thereof
CN101538136A
Anti-skid cement mortar and preparation method thereof
CN104556883A
Phosphorus-magnesium-based cement gunning material, and preparation method and application thereof
CN109694231A
Waterproof dry-mixed mortar and production process thereof
CN112794686A
Ultrahigh-toughness cement-based composite material used in ejection, and ejection process thereof
CN104150845A